Self-reported adherence to iron-folic acid supplementation and its associated factors among pregnant women attending antenatal care in Tamale Metropolis, Ghana - Matthew Yosah Konlan, MPH; Hilarius A. K. Abiwu; Martin Nyaaba Adokiya, PhD (World Nutrition, 2023)
Background This study assessed self-reported adherence to iron-folic acid supplementation and its associated factors among pregnant women attending antenatal care in Tamale Metropolis, Northern Ghana. Methods This was a health facility-based cross-sectional design. A total of 389 pregnant women attending antenatal care (ANC) were consented and recruited to participate in the study, using systematic sampling. Data were collected using a questionnaire on socio-demographic characteristics, obstetric factors, iron-folic acid (IFA) supplements, and adherence (self-reported). Respondents who consumed ≥70% (5/7 per week) of IFA tablets were considered to be adherent and vice-versa. Logistic regression models were used to determine factors associated with IFA adherence. Results IFA adherence was 41% among the respondents. Using multivariate logistic regression, secondary education [AOR=1.37, (95% CI= 1.18-1.82)], having ≥4 ANC visits [AOR=1.44, (95% CI= 1.28-1.67)], urban residence [AOR=1.59, (95% CI= 1.36-1.97)] and receiving IFA supplements at a health facility [AOR=1.98, (95% CI=1.02-3.83)] were associated with higher IFA adherence. Conclusion Iron-folic acid adherence was low (41%). Education, residence, ANC visits and supply of IFA supplements at the health facility attended were associated with IFA adherence. Barriers to IFA adherence were mainly forgetfulness, unavailability of IFA, and perceived side effects.